Age of acquisition and allophony in Spanish-English bilinguals - Barlow, Jessica A. (Frontiers in Psychology, 2014)
This study examines age of acquisition (AoA) in Spanish-English bilinguals’ phonetic and phonological knowledge of /l/ in English and Spanish. In English, the lateral approximant /l/ varies in darkness by context (based on the second formant [F2] and the difference between F2 and the first formant [F1]), but the Spanish /l/ does not. Further, English /l/ is overall darker than Spanish /l/. Thirty-eight college-aged adults participated: 11 Early Spanish-English bilinguals who learned English before the age of 5 years, 14 Late Spanish-English bilinguals who learned English after the age of 6 years, and 13 English Monolinguals. Participants’ /l/ productions were acoustically analyzed by language and context. The results revealed a Spanish-to-English phonetic influence on /l/ productions for both Early and Late Bilinguals, as well as an English-to-Spanish phonological influence on the patterning of /l/ for the Late Bilinguals. These findings are discussed in terms of the Speech Learning Model and the effect of AoA on the interaction between a bilingual speaker’s two languages.